Comaparison study on oil stability by microwave oven and direct heating using UV-VIS Spectroscopy - 291542 Lee, Chooi Chooi; Azli Sulaiman, supervisor; Fakulti Sains (2006)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2006